Mencairkan Suasana, Melestarikan Budaya: Pelatihan Ice Breaking Berbasis Kearifan Lokal Jambi bagi Calon Guru Sejarah - Robbi Kurniawanti, Merci; Mustofa Meihan, Andre; Yosephine Sinurat, Junita; Rukmana, Lisa; Siregar, Isrina (Pendidikan Sejarah FKIP Universitas JAMBI, 2025)
Abstrak: : Effective learning does not only depend on mastery of the material and delivery methods, but is also greatly determined by a conducive classroom atmosphere that is responsive to the dynamics of the students. Therefore, the role of the teacher is not only limited to delivering material, but also as a facilitator who is able to create a conducive and interactive classroom atmosphere. One strategy for creating a fun and effective learning atmosphere is through the use of ice breaking techniques. The method used is ice breaking training based on local wisdom with stages of preparation, implementation, evaluation, and publication. The material presented covers the basic concepts of ice breaking, the importance of preserving local wisdom, and ice breaking based on Jambi local wisdom. The activity was packaged interactively through discussions, question and answer sessions, ice breaking, reflection, and practice in creating ice breaking based on local wisdom in Jambi for each group. The products of the activity were ice breaking modules and video documentation that can be used continuously. Thus, this activity was not only effective in improving the pedagogical competence of students as prospective history teachers but also capable of preserving local wisdom in the Jambi area. This program benefits students and universities, while also supporting the achievement of the university's Key Performance Indicators (KPIs). The outputs of this community service program include articles published in national journals with ISSN, publications in the mass media, and activity videos.